2007
DOI: 10.1029/2006ja012196
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the radiation belt source region by data assimilation

Abstract: [1] We describe how assimilation of radiation belt data with a simple radial diffusion code can be used to identify and adjust for unknown physics in the model. We study the dropout and the following enhancement of relativistic electrons during a moderate storm on 25 October 2002. We introduce a technique that uses an ensemble Kalman filter and the probability distribution of the forecast ensemble to identify if the model is drifting away from the observations and to find inconsistencies between model forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 46 publications
3
101
0
Order By: Relevance
“…DREAM performs data assimilation using an ensemble Kalman filter technique (Koller et al, 2007) by combining PSD data with a 1-D radial diffusion model. The input PSD data are converted from flux observations from three LANL-GEO satellites, one GPS satellite (ns41), and the POLAR spacecraft in the second half of 2002.…”
Section: Initial Condition and Outer Boundarymentioning
confidence: 99%
“…DREAM performs data assimilation using an ensemble Kalman filter technique (Koller et al, 2007) by combining PSD data with a 1-D radial diffusion model. The input PSD data are converted from flux observations from three LANL-GEO satellites, one GPS satellite (ns41), and the POLAR spacecraft in the second half of 2002.…”
Section: Initial Condition and Outer Boundarymentioning
confidence: 99%
“…More recent 3-D diffusion models now include cross-diffusion terms and have shown that such terms can be important to the evolution of the radiation belts (Xiao et al, 2010;Subbotin et al, 2010). The Dynamic Radiation Environment Assimilation Model (DREAM, Reeves et al, 2005) incorporates data assimilation to drive radial diffusion results towards more realistic values (Koller et al, 2007). Other models, such as the Radiation Belt Environment (RBE) model (Fok et al, 2008), use bounce-averaged kinetic representations of the belts along with time-accurate magnetic and electric field specifications instead of simpler diffusion equations.…”
Section: T Welling Et Al: Radbelt Verificationmentioning
confidence: 99%
“…They are in most cases 1-D, i.e. according to L * , where only radial diffusion is considered (Naehr and Toffoletto, 2005;Koller et al, 2007;Kondrashov et al, 2007). In Koller et al (2007) and Shprits et al (2007), data assimilation with a 1-D physical model has been used to study radial profiles of phase space density.…”
Section: S a Bourdarie And V F Maget: Electron Radiation Belt Datmentioning
confidence: 99%
“…according to L * , where only radial diffusion is considered (Naehr and Toffoletto, 2005;Koller et al, 2007;Kondrashov et al, 2007). In Koller et al (2007) and Shprits et al (2007), data assimilation with a 1-D physical model has been used to study radial profiles of phase space density. In the present paper, we describe a data assimilation tool based on the 3-D Salammbô code (Varotsou et al, 2005(Varotsou et al, , 2008 and an ensemble Kalman filter (Evensen, 1994).…”
Section: S a Bourdarie And V F Maget: Electron Radiation Belt Datmentioning
confidence: 99%